Pertimbangan Visual dan Fisiologis sebagai Kriteria Panen Kangkung Darat Akibat Pemberian Kapur Dolomit di Tanah Gambut - Djoko Eko Hadi Susilo (Anterior Jurnal, 2015)
The giving of dolomite lime as the treatment was done as many as 3 dose level, namely: D1 = 3 tons ha-1; D2 = 6 tons ha-1 and D3 = 9 tons ha-1 as many as 9 replications. Observation was done to height of plant (cm); the number of leaves (leave); the leaves area (cm2), the leaves area index (ILD), fresh weight of harvest (g), and the fresh harvest index (IP) at the age of 21 and 28 days after planting (DAP). Fresh crop harvesting of Kale (Kangkong) was done by repealed (destructive). The result of this study showed that based on visual estimation and consideration of physiological indicators of Kale (Kangkong) growth in peat soil because of the giving dolomite lime, then criteria for the crop was considered can be harvesting starting at age 21 DAP and it did not need to wait until the plant at ages 28 DAP on all doses of giving lime (3-9 tons ha-1) because it has a physiological growth that supports the harvest index that relatively high at 73.2–78.1% despite fresh harvest at age 28 HST also able to achieve a harvest index of 74.9–76.1%. The result of this study suggested that fresh harvesting of Kale (Kangkong) that was repealed (destructive) should be beginning about age 21 DAP when planted in peat soil by using dolomite lime with a dose of 3-9 tons ha-1.